2019
DOI: 10.1111/papr.12810
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Guided Percutaneous Peripheral Nerve Stimulation for the Treatment of Lower Extremity Pain: A Rare Case Report

Abstract: Objective This case report presents an application of percutaneous peripheral nerve stimulation to the right superficial peroneal nerve to treat a patient with chronic intractable L5–S1 radiculopathy pain that conventional treatment failed to ameliorate. Methods The patient underwent an uneventful implantation of a percutaneous peripheral nerve stimulator. The implanted lead (15 cm in length and 1.2 mm in diameter) containing the receiver coil and 3 stimulation electrodes (Bioness Stimrouter®, Valencia, CA, U.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…The use of ultrasound has allowed the development of percutaneous peripheral nerve stimulation. On the one hand, some therapists implant a percutaneous peripheral nerve stimulator to manage chronic pain, such as radiculopathy pain [32], neuropathic postamputation pain [33], or low back pain [34]. On the other hand, other clinicians use the US-guided PNM that allows for applying PES in close proximity to the nerve, with ultrasound guidance [13].…”
Section: Discussionmentioning
confidence: 99%
“…The use of ultrasound has allowed the development of percutaneous peripheral nerve stimulation. On the one hand, some therapists implant a percutaneous peripheral nerve stimulator to manage chronic pain, such as radiculopathy pain [32], neuropathic postamputation pain [33], or low back pain [34]. On the other hand, other clinicians use the US-guided PNM that allows for applying PES in close proximity to the nerve, with ultrasound guidance [13].…”
Section: Discussionmentioning
confidence: 99%
“…This nonpainful stimulation provided by PNS inhibits these interneurons, thereby decreasing or even interrupting the transmission of pain signals [6][7]. Moreover, some studies have suggested that PNS may also directly change the excitability of peripheral nerve fibers, increasing the threshold for nociceptive stimulation to occur [6][7][8][9]. Some previous studies have also suggested that this direct peripheral inhibition could happen through an alteration in the local concentrations of biochemical mediators that augment the pain response.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last 5 years, it has been gaining momentum in terms of the development of new indications as well as with regard to the accumulation of clinical experience. It may even be particularly effective either as an adjuvant to spinal cord stimulation (SCS) or as a stand-alone therapy when the pain is localized to a part of a single extremity [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…After extensive reading, 12 studies were excluded. Therefore, a total of eighteen (n = 18) studies [10][11][12][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] were included in the literature data mapping (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…From six experimental studies, five were randomized controlled trials [11,36,37,47,49] and one was a trial protocol [12] reporting no results. Thus, nine studies were case series [10,35,39,[41][42][43]45,46,48] and three articles described case reports [38,40,44].…”
Section: Study Designsmentioning
confidence: 99%